Barley SIX-ROWED SPIKE3 encodes a putative Jumonji C-type H3K9me2/me3 demethylase that represses lateral spikelet fertility. Issue 1 (December 2017) - Bull, Hazel; Casao, M. Cristina; Zwirek, Monika; Flavell, Andrew; Thomas, William; Guo, Wenbin; Zhang, Runxuan; Rapazote-Flores, Paulo; Kyriakidis, Stylianos; Russell, Joanne; Druka, Arnis; McKim, Sarah; et al.
Abstract The barley inflorescence (spike) comprises a multi-noded central stalk (rachis) with tri-partite clusters of uni-floretted spikelets attached alternately along its length. Relative fertility of lateral spikelets within each cluster leads to spikes with two or six rows of grain, or an intermediate morphology. Understanding the mechanisms controlling this key developmental step could provide novel solutions to enhanced grain yield. Classical genetic studies identified five majorSIX-ROWED SPIKE (VRS ) genes, with four now known to encode transcription factors. Here we identify and characterise the remaining majorVRS gene, VRS3, as encoding a putative Jumonji C-type H3K9me2/me3 demethylase, a regulator of chromatin state. Exploring the expression network modulated byVRS3 reveals specific interactions, both with otherVRS genes and genes involved in stress, hormone and sugar metabolism. We show that combining avrs3 mutant allele with natural six-rowed alleles ofVRS1 andVRS5 leads to increased lateral grain size and greater grain uniformity. TheVRS genes of barley control the fertility of the lateral spikelets on the barley inflorescence. Here, Bull et al. show thatVRS3 encodes a putative Jumonji C-type histone demethylase that regulates expression of otherVRS genes, and genes involved in stress, hormone and sugar metabolism.